A novel molecule targeting neutrophil-mediated B-1a cell trogocytosis attenuates sepsis-induced acute lung injury - Akama, Yuichi; Chen, Jespar; Jha, Alok; Lee, Yongchan; Ma, Gaifeng; Li, Jingsong; Murao, Atsushi; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2025)
Sepsis is a dysregulated immune response to infection. B-1a cells play a crucial role in maintaining immuno-physiologic homeostasis. Sialic acid-binding immunoglobulin-like lectin G (Siglec-G) regulates B-1a cell’s behavior and function. Trogocytosis is the process by which one cell acquires portions of another cell’s plasma membrane and cytoplasm through direct contact. During sepsis, neutrophils accumulate in the lungs and serosal cavities, while B-1a cells decrease. We hypothesized that neutrophil-mediated trogocytosis causes B-1a cell depletion in sepsis, and that targeting this process could preserve B-1a cells and attenuate sepsis-induced acute lung injury (ALI). Sepsis was induced in mice by cecal ligation and puncture (CLP). Twenty hours after CLP, B-1a cells (CD19+B220lo/-CD23-CD5+) in the pleural and peritoneal cavities were quantified, and neutrophil engulfment of B-1a cells as well as trogocytosis were assessed. We also examine the interaction between Siglec-G and the “don’t-eat-me” signal receptor, CD47. Our data showed that B-1a cell numbers and frequencies in the pleural and peritoneal cavities were significantly decreased in sepsis. Neutrophils co-cultured with B-1a cells significantly increased B-1a cell internalization via trogocytosis. We observed a strong binding interaction between Siglec-G and CD47, which facilitates neutrophil-mediated trogocytosis by compromising CD47 function. We discovered a novel 11-aa therapeutic peptide, named Compound 11 (C11), derived from the CD47 region interacting with Siglec-G. C11 effectively preserved B-1a cell populations, significantly reduced pro-inflammatory cytokine levels, alleviated ALI, and improved survival in sepsis. Our findings highlight the Siglec-G/CD47 axis on B-1a cells as a key regulator of neutrophil-mediated B-1a cell depletion. Targeting this pathway with C11 represents a promising therapeutic strategy to mitigate immune dysregulation and improve sepsis outcomes.